In vivo emergence of HIV-1 highly sensitive to neutralizing antibodies. - Marlén M I Aasa-Chapman; Kelly M Cheney; Stéphane Hué; Anna Forsman; Stephen O'Farrell; Pierre Pellegrino; Ian Williams; Áine McKnight (PLoS ONE)
Background The rapid and continual viral escape from neutralizing antibodies is well documented in HIV-1 infection. Here we report in vivo emergence of viruses with heightened sensitivity to neutralizing antibodies, sometimes paralleling the development of neutralization escape. Methodology/principal findings Sequential viral envs were amplified from seven HIV-1 infected men monitored from seroconversion up to 5 years after infection. Env-recombinant infectious molecular clones were generated and tested for coreceptor use, macrophage tropism and neutralization sensitivity to homologous and heterologous serum, soluble CD4 and monoclonal antibodies IgG1b12, 2G12 and 17b. We found that HIV-1 evolves sensitivity to contemporaneous neutralizing antibodies during infection. Neutralization sensitive viruses grow out even when potent autologous neutralizing antibodies are present in patient serum. Increased sensitivity to neutralization was associated with susceptibility of the CD4 binding site or epitopes induced after CD4 binding, and mediated by complex envelope determinants including V3 and V4 residues. The development of neutralization sensitive viruses occurred without clinical progression, coreceptor switch or change in tropism for primary macrophages. Conclusions We propose that an interplay of selective forces for greater virus replication efficiency without the need to resist neutralizing antibodies in a compartment protected from immune surveillance may explain the temporal course described here for the in vivo emergence of HIV-1 isolates with high sensitivity to neutralizing antibodies.